Clinical, Laboratory and Virological Characteristics of Patients with Positive Hepatitis B Surface Antigen - Hajra Noor, Sana Noor, Abdullah Tanveer, Faiz Ahmed Faiz, Shafqat Ur Rehman Orakzai, Humera Javed (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: Globally, Hepatitis B virus (HBV) infection is a major health issue contributing to various diseases such as hepatocellular carcinoma (HCC) and liver cirrhosis. Virus replication complex interaction with host immune system response causes dynamic interplay leading to HBV infection. In developing countries, HBV infection plays a significant role in higher rates of morbidities and mortalities. The present study aimed to assess the clinical, laboratory, and virological characteristics of patients with positive HBV surface antigen. Methodology: This cross-sectional study was carried out on 182 positive HBV surface antigen (HBsAg) in the department of Medicine, Social Security Hospital, Multan Road Lahore from April 2021 to March 2022. All the patients with positive HBsAg and negative hepatitis C were enrolled. Patients with a history of chronic liver disease, acute hepatitis B infection, and antiviral therapy were excluded. All patients underwent CBC, liver function tests, clinical evaluation, and abdominal ultrasonography examination, HBV serological marker’s assessment, HBV transmission risk factors, and HBV-DNA quantitative detection. SPSS version 25 was used for data analysis. Results: Out of 182 HBV infected patients, there were 162 (89%) males and 20 (11%) females. The overall mean age was 38.6 ± 8.6 years. The most prevalent complaint and common findings was arthralgia and hepatomegaly with reported incidence of 32 (17.6%) and 16 (8.8%) respectively. Based on ultrasonography imaging results, the incidence of normal liver, coarse liver, splenomegaly, and cirrhosis were found in 81.3% (n=148), 12.6% (n=23), 5.9% (n=11), and 6.6% (n=12) respectively. Based on laboratory results, normal alanine aminotransferase, normal aspartate aminotransferase, reduced serum albumin, and low platelet count were found in 76.9%, 84.8%, 4.9%, and 10.2% respectively. Regarding laboratory, clinical, and imaging characteristics, HBV-DNA positive and negative had no significant differences. Conclusion: The present study found that HBV infected patient’s clinical manifestations were fatigue, bleeding gums, abdominal pain and fatigue. Majority of patients had normal liver on liver function tests and ultrasonographic examination. Most patients had negative HBV infection antigen. Based on comparisons made between HBV-DNA negative and positive, no substantial variations were reported on laboratory, clinical, and imaging characteristics. Keywords: HBV antigen, Virological characteristics, HBV